Debt Limits in Fund-Supported Programs : Proposed New Guidelines. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Low-income countries (LICs) face significant challenges in meeting their development objectives, while maintaining a sustainable debt position. To address this dilemma, the international community has largely advocated recourse to concessional external finance. The Fund's existing policy and practice on external debt limits conforms to this preference.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet